A combined health action process approach and mHealth intervention to reduce sedentary behaviour in university students – a randomized controlled trial. Issue 6 (3rd June 2022) - Dillon, Kirsten; Rollo, Scott; Prapavessis, Harry
Abstract: Objective: This investigation evaluated the effectiveness of a Health Action Process Approach (HAPA) based planning intervention augmented with text messages to reduce student-related sitting time (primary outcome) and increase specific non-sedentary behaviours. Relationships between the HAPA volitional constructs and sedentary and non-sedentary behaviours were also explored. Design: University students ( M age = 21.13 y; SD = 4.81) were randomized into either a HAPA intervention (n = 28) or control (n = 33) condition. Main Outcome Measures: School-related sitting time, time spent in specific non-sedentary behaviours and HAPA volitional constructs were assessed at baseline, weeks 2, 4, 6 (post-intervention) and 8 (follow-up). Results: Significant group by time interaction effects favouring the intervention group were found for sitting time ( p = 0.004, ɳp 2 = 0.10), walking time ( p = 0.021, ɳp 2 = 0.06) and stretching time ( p = 0.023, ɳp 2 = 0.08), as well as for action planning ( p < 0.001, ɳp 2 = 0.17), coping planning ( p < 0.001, ɳp 2 = 0.20) and action control ( p < 0.001, ɳp 2 = 0.20). Significant correlations ( p < 0.05) were also found between the HAPA constructs and sitting-related outcomes. Conclusions: Combining a HAPA-based planning intervention with text messages can reduce student-related sitting time in university students. Supplemental data for this article is available online at https://doi.org/10.1080/08870446.2021.1900574 .